Using infrared thermal imaging technology to estimate the transpiration rate of citrus trees and evaluate plant water status - Zhao, Wenyi; Dong, Xiaohua; Wu, Zhengping; Wei, Chong; Li, Lu; Yu, Dan; Fan, Xu; Ma, Yaoming (Journal of hydrology (Amsterdam), 2022)
•Use the new model (the 3D-3T model) to estimate plant transpiration.•The Normalized Difference Ratio Index (NDRI) is proposed for the first time.•The 2D-3T model was converted to the 5P-3T model.•The temperature of the canopy was accurately obtained by a portable thermal imager. Crop transpiration is the main dissipation way of agricultural water. Accurate and effective estimation of crop transpiration is of great significance for the study of the carbon-water cycle relationship and efficient water-saving irrigation. This study uses infrared thermal imaging technology to accurately extract the average temperature of the plant canopy as a key input for the new model (three-dimensional temperature (3D-3T) model), which is an extension of the three-temperature (3T) model and applied to estimate the canopy transpiration rate of typical citrus trees (variety named Guoqing No. 1) from 8:00 to 18:00 on May 7 to 11, 2021. And a processing method for extracting green plants in visible-light images based on the Normalized Difference Ratio Index (NDRI) is proposed for the first time, which can distinguish green plants from other ground objects, backgrounds, and shadows in the visible-light image, and then help to accurately extract the average canopy temperature from infrared thermal images. For this experiment, the canopy structure characteristics of the selected experimental subjects and the measurement methods used were considered, so the 3D-3T model was converted to a 5-point three-temperature model (5P-3T model) to estimate the canopy transpiration rate of citrus trees and evaluate the plant water status, and then the sap flow measurement was used for validation. The results showed that: (1) The 3T model overestimated the transpiration rate of the citrus tree, while the 5P-3T model underestimated it. The estimated values of the 5P-3T model have a good correlation with the measured values of the packaged stem sap flow gauge method, with a determination coefficient (R2) of 0.72 and root mean square error (RMSE) of 0.35 mm/d. (2) In this model, the plant transpiration transfer coefficient (hat) can evaluate the water shortage of plants, where the value of hat increased with the aggravation of plant water stress. (3) The citrus trees have lower transpiration rates under water stress, ranging from 0.06 to 0.12 mm/h in the daytime (from 8-10 May 2021). The model used in this study only needs the input of temperature information and net radiation, and would not depend on aerodynamic resistance. The method in this paper can realize the non-contact and non-invasive measurement of crop transpiration, and it provides a feasible way to use a portable thermal imager to accurately obtain the temperature for estimating plant canopy transpiration rate.